2014
DOI: 10.1590/1413-78522014220400954
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sports on health of former professional soccer players in Brazil

Abstract: OBJECTIVE: To evaluate the social, economic and health aspects related to former professional soccer players in Brazil. METHODS: This was a cross-sectional study with the participation of 100 male Brazilian former professional soccer players. For characterization of the sample variables such as age, current and past weight, height, BMI (Body Mass Index) and player position were evaluated. In all analyzes it was considered P <0.05. RESULTS: In the group of former players evaluated, 78% were overweight and 4% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
1
12
0
2
Order By: Relevance
“…UK footballers received over twice the number of KIA injections during their playing careers than that reported in a study of 27 Brazilian ex-professional footballers and 30 non-sport controls, though that study was powered for KOA outcomes rather than IA injections, and the type of injection and injection frequency per season were unreported [12]. It was, however, similar to another study of Brazilian ex-footballers which reported 54% of players as having received IA injections.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…UK footballers received over twice the number of KIA injections during their playing careers than that reported in a study of 27 Brazilian ex-professional footballers and 30 non-sport controls, though that study was powered for KOA outcomes rather than IA injections, and the type of injection and injection frequency per season were unreported [12]. It was, however, similar to another study of Brazilian ex-footballers which reported 54% of players as having received IA injections.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, WADA and their anti-doping regulations simply did not exist for elite footballers who played professionally during the 1950s-1980s. Data on use of knee IA (KIA) injections in professional footballers are limited to small studies (n = 27-100) in which 44-54% received knee IA (KIA) injections during their career and reported long-term impaired knee-health related quality of life, including 97% experiencing KP [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Apesar dos achados do presente estudo apontarem para indicadores de qualidade de vida e saúde mental na população investigada, deve-se considerar os estudos de Arliani et al (2014) com ex-jogadores de futebol que indicaram ganho de peso após a aposentadoria, elevado número de infiltrações de medicamentos no joelho durante a carreira e dor crônica nesta articulação após o término da carreira. A importância de se investigar a qualidade de vida dos atletas é apontada por Dos Santos (2015) que destaca que a investigação da temática é rara na área do esporte e a maioria dos estudos quando a investiga relaciona com a lesão.…”
Section: Resultsunclassified
“…Na tentativa de ampliar o entendimento do atleta de alto rendimento, Gucciardi et al (2016) propõem que a resistência mental, que seria a capacidade de gerenciar o estresse e a ansiedade, pode se apresentar como importante indicador de saúde mental ou facilitador da sua realização. Essa complexidade pode ser observada no estudo de Arliani et al (2014) que encontraram importantes indícios de baixa qualidade de vida e saúde física entre ex--jogadores profissionais de futebol no Brasil, como por exemplo, 78% apresentaram sobrepeso, 4% foram considerados obesos e 97% dor crônica na articulação do joelho após o término da carreira. Por sua vez, o estudo de Cevada et al (2012) encontraram melhores indicadores dos aspectos emocionais e saúde geral de ex-atletas quando comparado com não atletas.…”
Section: Introductionunclassified
“…Despite the huge increase in women's football in recent years, 80% of football players are still men. 1,2 The death of several athletes during football matches due to heart problems has caused great concern and prompted discussion in both FIFA (Fédération Internationale de Football Association) and medical societies. In fact, a survey conducted by the former indicated an average rate of one sudden death per month during football matches in the last 10 years.…”
Section: Introductionmentioning
confidence: 99%